The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 Please make a donation to keep the OEIS running. We are now in our 56th year. In the past year we added 10000 new sequences and reached almost 9000 citations (which often say "discovered thanks to the OEIS"). Other ways to donate

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A318008 G.f. A(x) satisfies: A( A( x - x^2 ) ) = x + x^2. 3
 1, 1, 1, 2, 4, 9, 21, 50, 122, 302, 758, 1928, 4958, 12849, 33509, 88122, 233810, 621022, 1641150, 4411180, 12364368, 33073210, 71807506, 206985492, 1354944972, 3153779248, -33794258600, -62697691948, 2524565441138, 5004344042337, -186642439700891, -368380986364150, 16196862324254354, 32039943659306982, -1602823227559245434 (list; graph; refs; listen; history; text; internal format)
 OFFSET 1,4 COMMENTS a(2*n-1) = A277292(n). a(2^k-1) = 1 (mod 2) and a(2^(k+1)-2) = 1 (mod 2) for k >= 1, and a(n) is even elsewhere (conjecture). LINKS Paul D. Hanna, Table of n, a(n) for n = 1..300 FORMULA G.f. A(x) satisfies: (1) A(-A(-x)) = x. (2a) A(A(x)) = 2*C(x) - x, where C(x) = x + C(x)^2 is a g.f. of the Catalan numbers (A000108). (2b) A(A( x - x^2 )) = x + x^2. (2c) A(A( x/(1+x)^2 )) = (x + 2*x^2)/(1+x)^2. (3a) (A(x) - A(-x))^2 = 2*(A(x) + A(-x)). (3b) A(x)^2 - 2*A(x) - 2*A(x)*A(-x) + A(-x)^2 - 2*A(-x) = 0. Define B(x) = (A(x) - A(-x))/2 and Catalan series C(x) = x + C(x)^2, then (4a) B(x)^2 = (A(x) + A(-x))/2. (4b) A(x) = B(x) + B(x)^2. (5a) B( A(x - x^2) ) = x. (5b) B( A(x) ) = C(x). (6a) A( B(x) - B(x)^2 ) = x. (6b) B( B(x) + B(x)^2 ) = C(x). (6c) C( B(x) - B(x)^2 ) = B(x). EXAMPLE G.f.: A(x) = x + x^2 + x^3 + 2*x^4 + 4*x^5 + 9*x^6 + 21*x^7 + 50*x^8 + 122*x^9 + 302*x^10 + 758*x^11 + 1928*x^12 + 4958*x^13 + 12849*x^14 + 33509*x^15 + ... such that A(A(x - x^2)) = x + x^2. RELATED SERIES. (a) A(A(x)) = x + 2*x^2 + 4*x^3 + 10*x^4 + 28*x^5 + 84*x^6 + 264*x^7 + 858*x^8 + 2860*x^9 + 9724*x^10 + ... + 2*A000108(n-2)*x^n + ... (b) The odd bisection B(x) = (A(x) - A(-x))/2 begins B(x) = x + x^3 + 4*x^5 + 21*x^7 + 122*x^9 + 758*x^11 + 4958*x^13 + 33509*x^15 + 233810*x^17 + 1641150*x^19 + 12364368*x^21 + ... + A277292(n)*x^(2*n-1) + ... such that B(x)^2 yields the even bisection (A(x) + A(-x))/2 B(x)^2 = x^2 + 2*x^4 + 9*x^6 + 50*x^8 + 302*x^10 + 1928*x^12 + 12849*x^14 + 88122*x^16 + 621022*x^18 + 4411180*x^20 + ... + a(2*n)*x^(2*n) + ... thus A(x) = B(x) + B(x)^2. (c) Also, the Catalan series equals B( B(x) + B(x)^2 ) = x + x^2 + 2*x^3 + 5*x^4 + 14*x^5 + 42*x^6 + 132*x^7 + 429*x^8 + 1430*x^9 + 4862*x^10 + ... + A000108(n-2)*x^n + ... (d) Note that A(x - x^2) equals the series reversion of B(x): A(x - x^2) = x - x^3 - x^5 - x^7 + 3*x^9 + 11*x^11 - 9*x^13 + 71*x^15 - 1685*x^17 + 31683*x^19 - 845729*x^21 + 28968319*x^23 + ... where B( A(x  -x^2) ) = x and A( B(x) - B(x)^2 ) = x. PROG (PARI) /* Using A(A( x - x^2 )) = x + x^2. */ {a(n) = my(A=x+x*O(x^n)); for(i=1, n, A = A + (x+x^2 - subst(A, x, subst(A, x, x-x^2)) )/2 ); polcoeff(A, n)} for(n=1, 30, print1(a(n), ", ")) CROSSREFS Cf. A277292, A000108. Sequence in context: A092423 A238438 A257104 * A199410 A091600 A261232 Adjacent sequences:  A318005 A318006 A318007 * A318009 A318010 A318011 KEYWORD sign AUTHOR Paul D. Hanna, Sep 06 2018 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified November 29 22:55 EST 2020. Contains 338779 sequences. (Running on oeis4.)